Lights, Camera, Action: The Power of Verbs. Writing Strategies to Ensure Your Action Words Are Not Weakened by Sloppy and Careless Drafting - Heller, Thomas Allan; Zoyirova Abdijalilovna, Dilsuz (Collected Papers of Thomas A. Heller, 2025)
The parts of speech form the backbone of English discourse and writing. They consist of nouns, adjectives, verbs, adverbs, pronouns, articles, prepositions, conjunctions and interjections. This article focuses on verbs, which are generally action words. Verbs bring oral discourse and writing to life. Careless use of verbs does a major disservice to writing. It weakens writing and accordingly diminishes the overall vitality of the written word. The authors analyze the principal ways in which verbs are misused. They offer easy to understand, concrete examples of how to avoid the pitfalls of misusing verbs to ensure any subject, but particularly legal writing, will be as powerful and easy to understand as possible. Using verbs correctly is an important component of the Plain English Movement, whose goal has been to stamp out legalese.